Azerbaijan Republic : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2003)
This Report on the Observance of Standards and Codes data module provides a review of Azerbaijan's data dissemination practices against the IMF's General Data Dissemination System (GDDS), complemented by an in-depth assessment of the quality of the national accounts, consumer price index, producer price index, government finance, monetary, and balance-of-payments statistics using the Data Quality Assessment Framework. Azerbaijan meets and in many cases substantially exceeds the GDDS recommendations on periodicity and timeliness for its macroeconomic statistics. The three main agencies responsible for compiling macroeconomic data have broadly adequate legal powers.